Sacred scripture, sacred war: the Bible and the American Revolution - Byrd, James P. (Oxford University Press, 2013)
The curse of cowardice: the martial power of the sermon -- the Lord is a man of war: Moses, the Exodus, and the Spirit of 76 -- Cursed be he that keepeth back his sword from blood: Deborah, Jeremiah, and prophetic violence -- Teacheth my hands to war, and my fingers to fight: David's revolutionary heroism -- The liberty wherewith Christ hath made us free: Peter, Paul, and apostolic patriotism -- The fierceness and wrath of Almighty God: revelation in the revolution -- Epilogue: an American patriot's Bible